2019
DOI: 10.3928/00220124-20191115-09
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Factors Influencing Nurse Competence Through Nursing Profile Analysis

Abstract: Background: Nurse competence is a combination of knowledge, performance, skills, and attitudes that are required in fulfilling one's role as a nurse. So far, few comprehensive studies have explored the influencing factors of nurse competence. Method: The competence levels of 160 RNs in a Chinese hospital were evaluated using a questionnaire method, and the relationship between competence results and nursing characteristics was analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…26 According to the study of Jing et al, the current competencies of clinical nurses are still at an intermediate level. 27 Since the 21st century, there has been a gradual emergence of nurses of various specialties to develop higher nursing skills and possess higher clinical practice, teaching guidance, consultation, and research and information skills. 28 By further developing the advanced practice roles such as Clinical Nurse Specialist (CNS) developed by the nursing workforce, the professional nursing skills and knowledge they possess will not only enhance the nursing experience and meet the needs of the patient, but also improve the voluntary utilization of health care.…”
Section: The Nurses' Own Competencementioning
confidence: 99%
“…26 According to the study of Jing et al, the current competencies of clinical nurses are still at an intermediate level. 27 Since the 21st century, there has been a gradual emergence of nurses of various specialties to develop higher nursing skills and possess higher clinical practice, teaching guidance, consultation, and research and information skills. 28 By further developing the advanced practice roles such as Clinical Nurse Specialist (CNS) developed by the nursing workforce, the professional nursing skills and knowledge they possess will not only enhance the nursing experience and meet the needs of the patient, but also improve the voluntary utilization of health care.…”
Section: The Nurses' Own Competencementioning
confidence: 99%
“…The results showed that nurses with more professional experience, a higher academic degree, working in an environment with readily available recourses and technology, and having more ability to think critically are more competent (Rizany et al, 2018). The positive effect of increased nurses’ experience as well as their age on the competence level have been reported in several studies conducted in different regional and international countries (Aqtash et al, 2017; Halabi et al, 2021; Jing et al, 2019; Kirkpatrick et al, 2019). In regard to gender, some studies found that female nurses reported higher levels of competence than male nurses (Falk-Brynhildsen et al, 2019; Gardulf et al, 2016); while other studies found no association between gender and level of competence among nurses (Aqtash et al, 2017; Halabi et al, 2021).…”
Section: Introduction and Significancementioning
confidence: 99%
“…According to the WHO, investment in nurses will contribute to achieving sustainable development goals in health, education, gender equality, decent work, and economic growth (WHO, 2020). The International Council of Nurses (ICN), a federation of more than 130 nursing associations that represents millions of nurses, reports that there is a high international mobility among the nursing workforce (ICN, 2019). The proportion of expatriate nurses in the workforce varies worldwide, but many major healthcare systems employ a large proportion of expatriate nurses.…”
Section: Introduction and Significancementioning
confidence: 99%